An SBQ-R assessment of the impact of COVID-19 pandemic on the mental health of young adults in North India: COVID-19 pandemic and mental health - Rani, Deepika; Krishan, Kewal; Tumram, Nilesh; Parekh, Utsav; Kanchan, Tanuj (Acta Biomedica Atenei Parmensis, 2022)
Abstract Background and aim: During the COVID-19 pandemic in India, an increase in the number of suicides was observed in India. Therefore, the present study aims to explore various factors affecting the mental health of an individual and their consequences. Moreover, it has been attempted to assess the suicidal risk in the population of North India by using the Suicidal Behaviors Questionnaire-Revised (SBQ-R). Methodology: The young adults from the North Indian population belonging to the age group of 18 to 35 years (24.93±4.42 years) have been incorporated into the study. A total of 190 responses (102 males and 88 females) were recorded through online mode. The present questionnaire has incorporated the Suicidal Behaviors Questionnaire-Revised (SBQ-R) and some of the parameters taken from the psychology today online survey. Results: The demographic characteristics of the respondents were described by using frequencies and percentages, means, and standard deviations. Cronbach’s alpha, Kaiser-Meyer-Olkin (KMO), and the Bartlett sphericity were calculated. The mean SBQ-R score was recorded to be 4.62±1.5. Further, during the factor analysis with the principal component method, seven factors have explained the 70.797% of the cumulative variance with an eigenvalue of 1. Conclusions: The SBQ-R assessment revealed a minimal risk of suicidal behavior but the frequency distribution of the parameters taken for the psychological assessment has highlighted that anxiousness or worriedness has a significant impact on the mental health of the population at risk. Therefore, it is recommended that some precautionary measures, such as online mental health services, should be taken by the health ministry to keep the population healthy.